Applying food systems thinking in recreational fisheries: The case of shore fishing in Detroit, Michigan - Emma D. Rice; Vivian M. Nguyen; Leandro Castello; Mahatub Khan Badhon; Elizabeth A. Nyboer (Marine Policy, 2026)

Assessment of the polyphenol recovery from white wine lees via non-ionic polymeric resins - Martina Gaglianò; Antonio D. Rodriguez-Lopez; Carmela Conidi; Alfredo Cassano; Giuseppina De Luca; Esperanza M. Garcia-Castello (Journal of Food Engineering, 2025)

Opportunities to better integrate inland fish and fisheries in multilateral environmental agreements - Abigail J. Lynch; Devin Bartley; T. Douglas Beard, Jr.; Gabriel Borba; Steven J. Cooke; Ian G. Cowx; Vittoria Elliott; Holly Embke; Edith Gondwe; Zeb Hogan; Jonathan G. Low; Jamie C. Madden; et al. (Environmental Science & Policy, 2025)

Corrigendum to “Scuba diving pressure is not responsible for decadal coral decline in the Bonaire National Marine Park” [J. Nat. Conser. 86 (2025) 126905] - Tara R.G. Williams; Julie P. Hawkins; Sofia Castello y Tickell; Callum M. Roberts (Journal for Nature Conservation, 2025)

Comanagement and reconciling of ecological and economic benefits in an Amazonian freshwater fishery - Monalisa R. O. Silva; Leandro Castello; Carolina T. Freitas; João V. Campos‐Silva; Carlos A. Peres; Evlyn M. L. M. Novo (Conservation Biology, 2025)
Freshwater ecosystems contribute substantially to the global fish catch. However, freshwater fisheries face growing human pressures and are underrepresented in global analyses and conservation strategies. Attempts to reconcile conservation and human welfare goals in fisheries have led to comanagement by the government and local communities, along with other stakeholders, but assessments of its effectiveness in freshwater fisheries are lacking. We investigated the effectiveness of comanagement in freshwater fisheries by assessing ecological (fish catch) and economic (fishing revenue) outcomes in a major tributary of the Amazon Basin. Fisheries comanagement in the Amazon is typically implemented through an approach developed by riverine communities called lake management in which floodplain lakes are categorized as open access, subsistence, or protected. Each category has different levels and types of fishing pressure. We analyzed data (e.g., fishing data and management rules) from 1607 fishing trips of 198 fishers over 5 years in 30 riverine communities in 74 floodplain lakes (20 open access, 33 subsistence, and 21 protected). Lake comanagement increased fish catch in protected lakes over time by 12% (2.4 kg) compared with subsistence lakes and by 13% (2.6 kg) compared with open‐access lakes ( p = 0.03). Increased fish catch in protected lakes was mainly due to limits on fishing effort. Fishing revenue was 63% greater in protected lakes than in open‐access lakes ( p

Fishing shrinks the size structure of exploited coral reef fishes in Brazil - Madeline V. Wood; Felipe M. Carvalho; Leandro Castello (Fisheries Research, 2024)

A second update to the checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; G. Calvia; et al. (Plant Biosystems, 2024)

A second update to the checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; M. Castello; et al. (Plant Biosystems, 2024)

A Synthesis of the Ecology and Conservation of Pseudoplatystoma Catfishes in the Neotropics - Luciana A. Pereira; Leandro Castello; Donald J. Orth; Fabrice Duponchelle; Eric M. Hallerman (Fishes, 2023)
Species of the genus Pseudoplatystoma, the long-whiskered catfishes, are important in commercial and recreational fisheries in South America, and some species have become key to regional aquaculture. Some species of the genus are under pressure due to overfishing and the negative impacts of dams. Six questions are asked in this review: (i) What species are in the genus, and where are they distributed? (ii) What are the life histories and ecologies of Pseudoplatystoma species? (iii) What are the patterns of somatic growth for these species? (iv) What is known about the biomass, production, and population dynamics of Pseudoplatystoma? (v) What is the geographic distribution of genetic variation within Pseudoplatystoma species? (vi) What are the threats to the conservation of these species? The taxonomy of the genus currently includes eight species, respectively, distributed over the Orinoco, Amazon, Paraná, and São Francisco basins. Pseudoplatystoma catfishes typically exhibit longitudinal migrations for reproduction and lateral migration for feeding, but these patterns may vary among populations. The size of the first maturation of these catfishes varies between 57 cm to 82 cm in total length. Five of the eight species spawn during the rising water season. Pseudoplatystoma species can grow to about 130 cm in total length and 100 Kg in weight and live until 30 years of age, depending upon the species. Biomass production and population dynamics of these catfishes have not yet been fully described. Their life-history characteristics indicate that they are periodic strategists with associated population recruitment dynamics. Population genetic patterning varies among Pseudoplatystoma species, with some degree of homing behavior and genetic differentiation among populations, indicating the need for management by applying the Management Unit and perhaps Evolutionary Significant Unit concepts. The main threats to the persistence of these catfishes are overfishing and alterations in and obstruction of river flow due to the construction of hydropower dams. After synthesizing existing information on species of the genus Pseudoplatystoma, we offer suggestions for future research to fill critical gaps in the knowledge of this group.

The stock assessment theory of relativity: deconstructing the term “data-limited” fisheries into components and guiding principles to support the science of fisheries management - Jason M. Cope; Natalie A. Dowling; Sybrand A. Hesp; Kristen L. Omori; Pia Bessell-Browne; Leandro Castello; Rowan Chick; Dawn Dougherty; Steven J. Holmes; Richard McGarvey; Daniel Ovando; Josh Nowlis; et al. (Reviews in Fish Biology and Fisheries, 2023)

The ten steps to responsible Inland fisheries in practice: reflections from diverse regional case studies around the globe - Steven J. Cooke; Elizabeth Nyboer; Abigail Bennett; Abigail J. Lynch; Dana M. Infante; Ian G. Cowx; T. Douglas Beard; Devin Bartley; Craig P. Paukert; Andrea J. Reid; Simon Funge-Smith; Edith Gondwe; et al. (Reviews in Fish Biology and Fisheries, 2021)

Incidence of enterovirus in patients with acute gastroenteritis - Z. Pérez-Martínez; M. E. Álvarez-Argüelles; S. Rojo-Alba; C. Castello-Abietar; J. A. Boga; A. Morilla-Morilla; A. Vivanco-Allende; J. Rodríguez-Suárez; M. A. Alonso-Álvarez; S. Melón (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Large-scale Degradation of the Tocantins-Araguaia River Basin - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Alberto Akama; José Dilermando Andrade Filho; Valter M. Azevedo-Santos; Marcus Vinicius Moreira Barbosa; Luis Mauricio Bini; Marcelo Fulgêncio Guedes Brito; Carlos Roberto dos Anjos Candeiro; Érica Pellegrini Caramaschi; Priscilla Carvalho; Rodrigo Assis de Carvalho; et al. (Environmental Management, 2021)

More nature in the city - G Capotorti; S Bonacquisti; L Abis; I Aloisi; F Attorre; G Bacaro; G Balletto; E Banfi; E Barni; F Bartoli; E Bazzato; M Beccaccioli; et al. (Plant Biosystems, 2020)

Recovery of Arapaima sp. populations by community‐based management in floodplains of the Purus River, Amazon - T. A. Petersen; S. M Brum; F. Rossoni; G. F. V. Silveira; L. Castello (Journal of Fish Biology, 2016)
In the present study a unique dataset on population abundance in various community‐based management ( CBM ) and non‐ CBM areas is analysed to address the question of whether CBM can recover overexploited populations of Arapaima sp. in river‐floodplain ecosystems. All non‐ CBM areas possessed depleted Arapaima sp. populations with a mean density of 0·01 individuals ha −1 . Arapaima sp. population densities in all CBM areas changed over time from depleted to overexploited or well managed status, with a mean rate of increase of 77% year −1 . Rates of Arapaima sp. population recovery in CBM areas differed, probably reflecting differences in ecosystem productivity and compliance with management regulations. These results indicate that CBM schemes can be effective tools for the recovery and conservation of fish populations with non‐migratory life cycles in tropical river‐floodplain ecosystems.

The expanding universe of ribonucleoproteins: of novel RNA-binding proteins and unconventional interactions - Benedikt M. Beckmann; Alfredo Castello; Jan Medenbach (Pflügers Archiv - European Journal of Physiology, 2016)

Dealing with temporal variation and different life stages of whitemouth croaker Micropogonias furnieri (Actinopterygii, Sciaenidae) in species distribution modeling to improve essential estuarine fish habitat identification - M. D. P. Costa; J. H. Muelbert; J. P. Vieira; J. P. Castello (Hydrobiologia, 2015)

Are Red Lists really useful for plant conservation? The New Red List of the Italian Flora in the perspective of national conservation policies - G. Rossi; C. Montagnani; T. Abeli; D. Gargano; L. Peruzzi; G. Fenu; S. Magrini; M. Gennai; B. Foggi; R.P. Wagensommer; S. Ravera; A. Cogoni; et al. (Plant Biosystems, 2014)

Differential Responses of Hippocampal Neurons and Astrocytes to Nicotine and Hypoxia in the Fetal Guinea Pig - Tamara Blutstein; Michael A. Castello; Shaun S. Viechweg; Maria M. Hadjimarkou; Joseph A. McQuail; Mary Holder; Loren P. Thompson; Jessica A. Mong (Neurotoxicity Research, 2013)

The polar lichens Caloplaca darbishirei and C. soropelta highlight the direction of bipolar migration - U. Søchting; M. Castello (Polar Biology, 2012)

Winter precipitation on the US Pacific coast and El Niño–southern oscillation events - Amy F. Castello; M. L. Shelton (International Journal of Climatology, 2004)
Winter precipitation increases as much as seven times from south to north along the US Pacific coast. For 1948–95, nine coastal grid points are used to identify spatial and temporal winter precipitation variations and to assess atmospheric circulation influences on precipitation variability. A strong negative correlation to the northwest of each precipitation grid point is revealed by one‐point correlation maps of precipitation at a given coastal grid point and 700 hPa geopotential heights at 288 grid points. The strength of the correlation decreases from north to south, and the northernmost precipitation grid point displays a correlation pattern nearly opposite that of the southernmost precipitation grid point. El Niño events are related to greater than average precipitation south of 43°N along the US Pacific coast. The largest negative height anomalies during an El Niño year are centred over the North Pacific Ocean west of Oregon. La Niña events display an asymmetric pattern relative to El Niño, with below‐normal rainfall along the California coast south of 41°N and above‐normal precipitation along coastal Oregon and Washington. La Niña years have negative 700 hPa geopotential height anomalies over the Gulf of Alaska. These characteristics delimit the region between 41 and 43°N as the transition zone defining El Niño–southern oscillation influences along the US Pacific coast. Copyright © 2004 Royal Meteorological Society

Spatio-temporal distribution of seismic activity during the Umbria-Marche crisis, 1997 - A. Deschamps; F. Courboulex; S. Gaffet; A. Lomax; J. Virieux; A. Amato; A. Azzara; B. Castello; C. Chiarabba; G.B. Cimini; M. Cocco; M. Di Bona; et al. (Journal of Seismology, 2000)

Detection of tomato mosaic tobamovirus RNA in ancient glacial ice - John D. Castello; Scott O. Rogers; William T. Starmer; Catharine M. Catranis; Lijun Ma; George D. Bachand; Yinghao Zhao; James E. Smith (Polar Biology, 1999)

Ganciclovir therapy for cytomegalovirus-associated liver disease in immunocompetent or immunocompromised children - G. Nigro; A. Krzysztofiak; U. Bartmann; A. Clerico; E. Properzi; S. Valia; M. Castello (Archives of Virology, 1997)